THE EFFECT OF DEBT EQUITY RATIO , RETURN ON EQUITY , NET PROFIT MARGIN ON STOCK PRICES - Ono Tarsono (International Journal of Social Science, 2021)
This study aims to analyze DER, ROE, on stock prices on the Indonesia Stock Exchange during the 2015-2019 period. The analytical research technique used is multiple linear regression analysis. The results of this study indicate that the Debt Equity Ratio, Return On Equity, Net Profit Margin have an effect on stock prices . Based on the coefficient of determination of the influence of Debt Equity Ratio, Return On Equity, Net Profit Margi has an influence of 54.6%. It is recommended that investors and potential investors if they want to invest are expected to be able to see and analyze the ratios that affect the overall stock price.